Faktor-faktor yang Berhubungan dengan Pengetahuan Ibu Tentang Pijat Bayi Usia 0-12 Bulan - Pratiwi, Rina; Ari Andayani (Universitas Ngudi Waluyo, 2023)
Infancy is a stage where growth and development occurs very quickly, up to the age of 12 months (Dewi, 2018). According to WHO, 2017, globally around 20-40% of infants aged 0-3 years experience delays in the development process. National data according to the Indonesian Ministry of Health that in 2014, 13% - 18% of children under five in Indonesia experienced growth and development disorders (WHO, 2019). The purpose of this study is to determine the factors related to mother's knowledge about massage for babies aged 0-12 months in Saka Village, Sangkulirang District, East Kalimantan. This type of quantitative research uses a descriptive analytic design with a cross sectional approach. The population in this study were all mothers who had babies 0-12 months as many as 50 people. sampling technique using Accidental Sampling. the majority had good knowledge, there were 36 (72.0%) mothers. While the majority of respondents had received information on infant massage 0-12 months, there were 46 people (92.0%). Based on the level of education, the majority of respondents with higher education (SMA, PT) were 35 (70.0%). Most of the respondents are in late adulthood (26-35 years), namely there are 35 people (70.0%). There is a relationship between knowledge and sources of information (P-value: 0.029 and OR 9.45), education (P-value: 0.000 and OR 66.0 ), and age (P-value: 0.009 and OR 0.181). The conclusion is all variables have a relationship with knowledge of infant massage. Abstrak Masa bayi merupakan tahapan dimana pertumbuhan dan perkembangan terjadi sangat cepat, hingga usia 12 bulan (Dewi, 2018). Menurut WHO, 2017, secara global sekitar 20-40% bayi usia 0-3 tahun mengalami masalah keterlambatan dalam proses perkembangan. Data nasional menurut Kementrian Kesehatan Indonesia bahwa pada tahun 2014, 13%- 18% anak balita di Indonesia mengalami kelainan pertumbuhan dan perkembangan (WHO,2019). Tujuan dari penelitian ini Untuk mengetahui faktor-faktor yang berhubungan dengan pengetahuan ibu tentang pijat bayi usia 0-12 bulan Jenis penelitian kuantitatif menggunakan desain deskriptif analitik dengan pendekatan cross sectional. Populasi pada penelitian ini adalah semua ibu yang mempunyai bayi 0-12 bulan sebanyak 50 orang. teknik pengambilan sampel menggunakan Accidental Sampling. mayoritas berpengetahuan baik ada 36 (72,0%) Ibu. Sedangkan mayoritas responden pernah mendapatkan informasi pijat bayi 0-12 bulan ada 46 orang (92,0%). Berdasarkan tingkat pendidikan mayoritas responden berpendidikan tinggi (SMA, PT) ada 35 (70,0%). Sebagian besar usia responden masuk dewasa akhir (26-35 tahun) yaitu ada 35 orang (70,0%). Ada hubungan pengetahuan dengan sumber infomasi (P-value: 0,029 dan OR 9,45), pendidikan (P-value: 0,000 dan OR 66.0 ), dan umur (P-value: 0,009 dan OR 0,181). seluruh variable terdapat hubungan dengan pengetahuan pijat bayi.